The natural history of Calyptraea aurita (Reeve, 1859) from Southern Chile (Gastropoda, Calyptraeidae) - Holtheuer, Jorge; Aldea Venegas, Cristian Leonardo; Schories, Dirk; Gallardo, Carlos S. (My University, 2018)
Hard bottom communities of the Reloncavi Estuary and adjacent areas, Region de los Lagos, Chile (42 degrees S), were studied between 2008 and 2011. All hard substrates between the lower intertidal and 25 m depth were dominated by the calyptraeid gastropods, Crepipatella dilatata and C. fecunda. Epibenthic coverage of the hard bottoms markedly decreased further down with the exception of vertical cliffs. In a depth range between 26 to 48 m repeatedly dense patches of another calyptraeid species, Calyptraea aurita (Reeve, 1859), were observed. Densities reached up to 1475 individuals m(-)(2) and covered up to 50 % of the rock surfaces. In shallower depths C. aurita was not present. However, despite its huge abundance, C. aurita has not been documented for more than 150 years in the southeastern Pacific, being described superficially by Reeve, through only shell characteristics. Here, we redescribe and compare it with other members of the family Calyptraeidae through characteristics of shell, radula, and soft parts, including also details of the egg mass and intracapsular development of their embryos. Males were mobile and females sessile. Shell size ranged from 6.6 to 12.4 mm for immature individuals, from 10.6 to 24.9 mm for males, 15.1 to 25.9 mm for intersex individuals, and from 21.0 to 39.6 mm for females. Up to three individuals stacked together were found, always presenting a female at the base with up to a maximum of two male individuals above. Laboratory studies demonstrated that C. aurita has an indirect larval development, liberating planktotrophic larvae with a bilobed ciliated velum into the water column. A transplantation experiment demonstrated that survival, growth, and reproduction of C. aurita is also possible in depths shallower than its normal distribution. The geographic distribution of C. aurita, was previously only known as being from Valparaiso (33 degrees S) and is now extended down to the Reloncavi Sound (41 degrees S).
Keywords: calyptraeid gastropod; external morphology; growth; radula; reproduction; shell; transplantation